EU researchers offer sustainable solutions for European manufacturing. (Research'eu results magazine)
During its final conference held in Brussels on 18 October 2016, the EU-funded USE-IT-WISELY project outlined its innovative frameworks and tools that will equip European manufacturers to effectively compete in an increasingly globalised world economy.